2009
DOI: 10.1099/jmm.0.007906-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of candidaemia by real-time PCR detection of Candida DNA in blood samples

Abstract: This study prospectively evaluated an 18S rRNA gene-targeted real-time PCR approach in comparison with standard blood culture (BC) diagnostics for rapid diagnosis of candidaemia in a large study population of 384 patients, including 902 whole blood samples from 468 infectious episodes (IEs) of 329 adults and 55 children with haematological malignancies and various forms of immunodeficiency, and intensive care unit patients. Seven out of eight BC-proven cases (87.5 %) of candidaemia and seven out of twelve BC-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…Multiple studies have evaluated the performance of PCR tests for the diagnosis of invasive Candida infections in patient populations (4,118,(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202) (studies are summarized in Table 5). The ranges of reported sensitivity and specificity values are 56.2 to 100% and 54 to 100%, respectively.…”
Section: Pcrmentioning
confidence: 99%
“…Multiple studies have evaluated the performance of PCR tests for the diagnosis of invasive Candida infections in patient populations (4,118,(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202) (studies are summarized in Table 5). The ranges of reported sensitivity and specificity values are 56.2 to 100% and 54 to 100%, respectively.…”
Section: Pcrmentioning
confidence: 99%
“…We are not yet able to estimate the value of finding fungal DNA from patient blood in this outbreak, given the small sample size and the fact that there is little knowledge of the natural history of the infection, the fungal pathogenesis and innate host defense, or the therapeutic response and prognosis. However, detecting fungal DNA from blood is valuable in assisting rapid and accurate diagnosis for some types of invasive fungal infections, such as invasive candidiasis and invasive aspergillosis (13)(14)(15)(16). Regardless of sample size, 29 to 50% (depending on the cutoff) of tested blood being fungus positive indicated that having an insidious fungal infection may not be just an incidental event in this vulnerable population.…”
mentioning
confidence: 99%
“…-Examen micológico directo y cultivo de cualquier zona afectada según la evaluación clínica (líquido articular, líquido peritoneal, tejido obtenido por biopsia). -Las técnicas de diagnóstico molecular y determinación de antígenos están bajo evaluación en RN para complementar el diagnóstico de CI 23,24 .…”
Section: Estudio De Una Potencial Efiunclassified